Pembelajaran Model Blended Learning - Husni Idris (IAIN Manado, 2011)
A blended approach to a traditional, face to face course might mean that the class meets once per week instead of the usual three-session format. Learning activities that otherwise would have taken place during classroom time can be moved online. In addition, the terms